2017
DOI: 10.1177/096739111702500706
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Conductivity and Microwave Absorption Behavior of Polyaniline Nanocomposites after Chemical Treatment

Abstract: In this study, the hexanoic acid (HA) doped Polyaniline (PAni) nanocomposites which comprise aniline (Ani) as a monomer, titanium dioxide (TiO2) as a dielectric material and fullerene (C60) as a carbonaceous material with and without treated with different types of sulfonic groups: dioctyl sodium sulfosuccinate (AOT), sodium dodecylbenzene sulfonicate (DBSA) and camphorsulfonic acid (CSA) were synthesized through the template-free method. The fourier transform infrared (FTIR), ultraviolet-visible (UV-vis), x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Figure 5(A) shows the IR spectra of six samples, respectively. The intensity of two C 60 characteristic peaks is at 527 and 577 cm ‐1 [ 26, 27 ] Compared with pure C 60 , the increased peak in all PANI/C 60 samples was the same as that in pure PANI. The main peaks showed at 3436, 1560 and 1473 cm −1 corresponding to NH stretching vibration, quinone, and benzene ring deformation, [ 28–30 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5(A) shows the IR spectra of six samples, respectively. The intensity of two C 60 characteristic peaks is at 527 and 577 cm ‐1 [ 26, 27 ] Compared with pure C 60 , the increased peak in all PANI/C 60 samples was the same as that in pure PANI. The main peaks showed at 3436, 1560 and 1473 cm −1 corresponding to NH stretching vibration, quinone, and benzene ring deformation, [ 28–30 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pure C 60 has sharp diffraction peaks at 2θ = 11 , 17.5 , and 21 . [27] The pure PANI has obvious diffraction peaks at 2θ = 20 and 25 . [31,32] As can be seen from the patterns, with the increase of the concentration of doped acid, it can be seen that the remaining samples, like pure PANI, have obvious diffraction peaks at 2θ = 20 and 25 , indicating that the PANI has a certain orientation ordering and the crystallinity increases.…”
Section: The Structure Of the Pani/c 60 Compositesmentioning
confidence: 99%
“…CMC-PANI was attributed to the periodicity perpendicular to the PANI chain direction [58]. These peaks demonstrated that PANI was successfully polymerized inside BC-PANI and CC-PANI.…”
Section: Plos Onementioning
confidence: 86%